Combined Levitation Design and Control of a Novel M-DOF Actuator Based on Air Bearing and Electromagnetic Principle - LI, Zheng (Elektronika ir Elektrotechnika, 2013)
Supporting and levitation control are important for actuators or motors with complicated structures. Based on the presented configuration design, the simplified torque calculation model and non-linear system dynamic model have been proposed, and air bearing combined with magnetic levitation mechanism is developed for alleviating the friction and resistance to improve the dynamic performance of this M-DOF actuator. The fluid field model is built in computational fluid dynamics software. Different structure parameters and conditions are computed and compared with the vortex torque characteristics and pressure distribution. A linear mathematical model of the magnetic levitation force is deduced and corresponding control scheme with power drive unit is discussed. Experiment results show that the actuator can effectively implement 3-DOF motion combined with the combined levitation modes, and that the proposed approach can be applied to m-DOF actuators of the same kind effectively. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.1387